Output power regulation system for portable micro fuel cell systems - Zhong, Shaoxuan; Yuan, Weijian; Liu, Xiaoqiang; Cao, Jiamu; Zhang, Yufeng (Frontiers in energy research, 2023)
This article presents an output power regulation system for micro fuel cells to help enhance the stability of the fuel cell in a portable micro power system. The structure of an MCU-controlled DC-DC converter is proposed. Then, the output characteristics of a selected fuel cell stack and the DC-DC converter’s power control functions are estimated by a system-level model. Based on the simulation results, the model provides a power regulation system which is implemented, and the test shows that it fulfills its intended function and the output power is regulated to a fixed level of 5 W–40 W with good efficiency.